STRATEGIES FOR DEVELOPING ISLAMIC ECONOMY THROUGH AI: A STUDY ON SUSTAINABLE HALAL INDUSTRY - Rina Ambarwati; Abu Naim; Dadang; Andika Mugi Gumilang; Fachmi Al Faroqi; Sapriyadi; Ervina Yennie Permananingrum; Sugiyono; Maman Supriatman; Agus Hermawan; Nor Fattah Ulinuha; Arswendo Susandi Nur (Berajah Journal, 2026)
With the increasing demand for goods and services that comply with Sharia principles, the halal industry is one of the important sectors in the global economy that continues to grow rapidly. However, issues such as lack of efficiency, transparency, and global competition still pose significant obstacles to progress. By using AI in the halal industry, this research aims to create an Islamic economic development strategy focused on achieving economic sustainability in line with the Sustainable Development Goals (SDGs). This research was conducted using a qualitative approach by carrying out case studies on several halal businesses in Indonesia. Observation, interviews, and document analysis are the methods used to collect data. This study examines how artificial intelligence technologies, such as machine learning, big data analytics, and blockchain, can enhance operational efficiency, ensure Sharia compliance, and increase the availability of halal products in the market. Research shows that the application of artificial intelligence in the halal industry can offer innovative solutions such as automatic halal certification management, increased transparency in the production process, and optimization of the halal supply chain. Strengthening regulations that support Sharia-based innovation and enhancing collaboration between the government, industry players, and artificial intelligence technology providers are some of the recommended development strategies. It is hoped that the implementation of these strategies will help in the development of an inclusive and sustainable economy while also enhancing the competitiveness of the halal industry in the global market. This research greatly contributes to the development of literature related to technology-based Islamic economics. This also serves as a practical guide for policymakers and players in the halal industry.